Chamba para comunicas: estrategia digital en linkedin - Sissa Machado, Arianna (2023)
As of today, university students don’t know where to start their search for formal jobs or think they will not find a decent one due to lack of experience. Based on this situation, Chamba para comunicas was created; a project that seeks to help future interns with backgrounds in creative majors to get a job under fair conditions and give them advice to improve their job profile. This project consists of a digital strategy for LinkedIn, which will allow students to become better prepared for the corporate world through articles, advice, job posting and content creation so they won’t have to accept unfair jobs just to get experience. In addition, I created a content grid to help increase followers and post impressions. Chamba para comunica’s value proposition makes it stand out from the competition: help is personalized to different individual needs, only jobs that meet the standards established by law and have fair remuneration are published and members of our community can post job offers.